A robust spectroscopic method for the determination of protein conformational composition – Application to the annealing of silk. (June 2018) - Belton, David J.; Plowright, Robyn; Kaplan, David L.; Perry, Carole C.
Graphical abstract: Abstract: The physical and mechanical properties of structural proteins such as silk fibroin can be modified by controlled conformational change, which is regularly monitored by Fourier transform infrared spectroscopy by peak fitting of the amide I band envelope. Although many variables affecting peak shape are well established, there is no fixed methodology to compare and follow secondary structural differences without significant operator input especially where low frequency spectral noise is a problem. The aim of this contribution is to establish a method for such analyses to be carried at high levels of autonomy to prevent subjective or erroneous fitting. A range of approaches was trialled with optimal peak parameters selected based on overall goodness of fit and reproducibility of fit of replicate sample spectra. The method was successfully tested against reference proteins having contrasting β content and the rationale for parameter selection is presented. Further, we applied this method to measure the effect of conformational change on the energy of the amide I band of silk fibroin during annealing. Energy changes were ca. 400 kJ mol −1 of fibroin. To confirm that this energy change was a consequence of increased hydrogen bonding we used a Thioflavin T staining method typically used to identify β aggregate type structures in amyloid plaques. We propose that the approach described herein can aid in the development of silk based materials for biomedical applications where tuning of the physical and mechanical properties of the silk are needed to guarantee optimum activity. Statement of Significance: The physical and mechanical properties of proteins including silk fibroin can be modified by controlled structural change, which is regularly monitored by Fourier transform infrared spectroscopy (FTIR) by peak fitting of the amide I band. Currently there is no fixed methodology to compare and follow secondary structural differences without significant operator input leading to subjectivity and error. This contribution establishes a method for such analyses to be carried at high levels of autonomy applicable to a wide range of proteins and the conformational changes have been quantified as a single energy change output, which clearly shows the progression of the annealing process used. We propose that the approach can help in the development of silk based materials for biomedical applications where tuning of the physical and mechanical properties of the silk are needed to guarantee optimum activity.